Cancer therapy by targeting the Warburg effect with miR-143 and response monitoring with 18F-FDG PET - Jung, Kyung-Ho; Lee, Kyung-Han (Translational Cancer Research, 2017)
miRNAs are non-coding short endogenous RNAs that act as negative regulators of gene expression by targeting mRNA (1). After its first discovery in C. elegans, a key paper confirmed the existence of many miRNAs in vertebrates, including humans (2). In subsequent years, miRNAs have emerged as critical players in modulating such key biological processes as cell proliferation and apoptotic death (1). More recently, several miRNAs are drawing attention for their roles in regulating glucose and energy metabolism (3,4).